PERFORMANCE AND STABILITY FOR GRAIN YIELD AND YIELD COMPONENTS OF SIX-ROW BARLEY CULTIVARS UNDER VARIOUS ENVIRONMENTS IN KURDISTAN REGION-IRAQ - Abdulla, A. A.; K. M. Mustafa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to investigate yield and yield components of barley (Hordeum vulgare L.) under six different environmental conditions E1- E6 including two sowing date S1 and S2 at three location (Qlyasan, Kanipanka, Chamchamal) in KIR using 10 barley cultivars (C), Numar, Rafidain, Al-warka, Al-Amal, IPPA 265, IPPA 99, Arivat (local), Samir, Qalay 1, and Ukraine (Common cultivated). Experiment was applied using to complete randomized blocks design. The stability analysis was done using the linear regression model. The differences between the means were compared through Duncan multiple range test. The results was revealed that the mean sum of squares due to cultivars, environment, and C x E were highly significant for all studied characters. The cultivar Numar which had highest mean grain yield (3.559) th-1, high bi value1.96 and low S2di 0.058) considered optimal yield stability cultivar. The combination C1E3 gave the top grain yielding (6.91 th-1) due to very high GS, high NS and good TGW performances.